Sialolithiasis. Issue 9 (September 2022) - Harrison, Patrick; Richards, Claire; Niziol, Rafal; Fry, Alistair
Sialolithiasis is one of the most common salivary gland diseases. It is characterised by salivary gland stones, also known as sioliths, which can block outflow of saliva from the salivary ducts. These stones are associated with pain and swelling as pressure in the ducts increases before, during and after eating foods, in what is known as 'mealtime syndrome'. Patients often present to primary care services. Symptoms overlap with symptoms of dental origin, hence, a discerning knowledge of this subject can aid swift referral and improve patient care.